2006
DOI: 10.1152/physiol.00012.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin: The Gray Eminence of the Cytoskeleton

Abstract: Cortactin, an actin filament-binding protein and target of multiple kinases, has emerged as a central element connecting signaling pathways with cytoskeleton restructuring. It is involved in a perplexingly diverse array of cellular processes, including cell motility, invasiveness, synaptogenesis, endocytosis, intercellular contact assembly, and host-pathogen interactions, where the common denominator appears to be a role in the coordination of membrane dynamics with cytoskeletal remodeling. Although in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
202
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(213 citation statements)
references
References 101 publications
8
202
0
3
Order By: Relevance
“…Cortactin was thought for years to be essential for processes involving Arp2/3 complex function, such as lamellipodia formation or receptor-mediated endocytosis 14 , and the finding that it was dispensable for these processes 10 was quite surprising, albeit consistent with earlier observations e.g. using Drosophila genetics 15 .…”
supporting
confidence: 68%
“…Cortactin was thought for years to be essential for processes involving Arp2/3 complex function, such as lamellipodia formation or receptor-mediated endocytosis 14 , and the finding that it was dispensable for these processes 10 was quite surprising, albeit consistent with earlier observations e.g. using Drosophila genetics 15 .…”
supporting
confidence: 68%
“…Subsequently, we found that the mechanism for channel suppression involves the dynamin-dependent endocytosis of Kv1.2 (2). That finding is particularly intriguing because cortactin's role in endocytosis is becoming increasingly apparent (3,4).…”
mentioning
confidence: 89%
“…The upstream regulator of Pfn-1 is not well identified. Because cortactin has been implicated in actin cytoskeletal remodeling (13,14), we hypothesized that contractile stimulation may promote the association of cortactin with Pfn-1, which may activate Pfn-1 in smooth muscle in response to contractile activation. To test this, HASM cells were stimulated with ACh (a stimulus implicated in airway tone and asthma) (38) for 5 min, or cells were unstimulated.…”
Section: Interaction Of Cortactin With Pfn-1 Is Enhanced In Smoothmentioning
confidence: 99%
“…Cortactin is an adapter protein that is able to regulate actin filament assembly and branching in in vitro studies as well as adhesion, migration, and endocytosis of nonmuscle cells (13,14). Cortactin undergoes phosphorylation on Tyr-421 in fibroblasts during cell migration, and this has been implicated in the activation of cortactin (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation